A New Collection of Pre-Socratic and Platonic Essays: Problems of Philosophical Papyrology and History of Ideas - Vassallo, Christian (Peitho. Examina Antiqua, 2013)
Richard Patterson, Vassilis Karasmanis, Arnold Hermann (eds.), Presocratics and Plato. Festschrift at Delphi in Honor of Charles Kahn, Las Vegas-Zurich-Athens 2012, pp. 599.